Risk of POP mixtures on the Arctic food chain - Villa, Sara; Migliorati, Sonia; Monti, Gianna Serafina; Holoubek, Ivan; Vighi, Marco (Environmental toxicology and chemistry, 2017)
The exposure of the Arctic ecosystem to persistent organic pollutants (POPs) was assessed through a review of literature data. Concentrations of 19 chemicals or congeneric groups were estimated for the highest levels of the Arctic food chain (Arctic cod, ringed seals, and polar bears). The ecotoxicological risk for seals, bears, and bear cubs was estimated by applying the concentration addition (CA) concept. The risk of POP mixtures was very low in seals. By contrast, the risk was 2 orders of magnitude higher than the risk threshold for adult polar bears and even more (3 orders of magnitude above the threshold) for bear cubs fed with contaminated milk. Based on the temporal trends available for many of the chemicals, the temporal trend of the mixture risk for bear cubs was calculated. Relative to the 1980s, a decrease in risk from the POP mixture is evident, mainly because of international control measures. However, the composition of the mixture substantially changes, and the contribution of new POPs (particularly perfluorooctane sulfonate) increases. These results support the effectiveness of control measures, such as those promulgated in the Stockholm Convention, as well as the urgent need for their implementation for new and emerging POPs. Environ Toxicol Chem 2017;36:1181-1192. © 2017 SETAC.
Keywords: Environmental Pollutants; látky znečišťující životní prostředí; Mixture; Arktida; ekosystém; Arctic Regions; polychlorované bifenyly; halogenované difenylethery; Seals, Earless; potravní řetězec; Arctic; Polychlorinated Biphenyls; Penalized regression smoothers; tuleňovití; zvířata; Risk assessment; medvědovití; Halogenated Diphenyl Ethers; Ursidae; Food Chain; Risk; riziko; Persistent organic pollutants (POPs); Ecosystem; Animals